2022
DOI: 10.1051/ocl/2021048
|View full text |Cite
|
Sign up to set email alerts
|

New approach for the elucidation of the phenomena involved in the operation of vegetable oil extraction presses

Abstract: In a context where the search for naturalness, the need to reduce the carbon footprint and the development of a decentralized crushing sector are intensifying, mechanical extraction is a technology that is regaining major importance for the industry. The performance of this technique remains far below what is desirable, while the understanding of the main phenomena involved in screw presses remains insufficient. This article, after a brief presentation of the state of the art of this discipline, presents a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The physical essence of the improvement made for the EK-75/1200 twin-screw extrusion press is confirmed and partially described when optimising the geometry of the screw shaft of the single-screw press reflected in the study (Carré, 2022). Namely, it indicates the generally accepted statements that high pressure is needed for maximum oil production.…”
Section: Resultsmentioning
confidence: 64%
“…The physical essence of the improvement made for the EK-75/1200 twin-screw extrusion press is confirmed and partially described when optimising the geometry of the screw shaft of the single-screw press reflected in the study (Carré, 2022). Namely, it indicates the generally accepted statements that high pressure is needed for maximum oil production.…”
Section: Resultsmentioning
confidence: 64%
“…5). In most of the papers with experimental studies (Evon et al, 2016;Carré, 2022), the oil pressing process was carried out under different operating conditions to evaluate their impact on oil yield, press capacity, energy consumption, etc. In S.M.…”
Section: Resultsmentioning
confidence: 99%
“…There are several purely mechanical extraction methods: cold pressing, pressing after cooking and double pressing (cold pressing followed by heat conditioning and a second pressing). Their performance in terms of residual oil content in the meal ranges from 9.9 to 16.3%, 9.7 to 15.7% and 8.7 to 13.5% residual oil (rapeseed), respectively [ 36 ]. The key to the press performance is the conversion of electrical energy into pressure rather than heat.…”
Section: Oilseed Extractionmentioning
confidence: 99%
“…Savoire et al [ 38 ] reported on the capacity, energy consumption and extraction efficiency of several commercially available industrial presses. The largest capacity solvent-free crushing units in the world process more than 250,000 tonnes but are mainly related to biodiesel production [ 36 ]. For these reasons, the new requirements for screw presses favour a higher capacity, lower horsepower consumption and easier maintenance.…”
Section: Oilseed Extractionmentioning
confidence: 99%
See 1 more Smart Citation